Potentially beneficial effects of rhamnose on skin ageing: an in vitro and in vivo study. (6th May 2019) - Pageon, H.; Azouaoui, A.; Zucchi, H.; Ricois, S.; Tran, C.; Asselineau, D.
Abstract: Objective: Recent findings showed that skin ageing preferentially affects human papillary dermal fibroblasts suggesting that the papillary dermis represents a critical zone altered by skin ageing. Based on these findings, we investigated the potential anti‐ageing effect of rhamnose. Methods: We investigated the potential anti‐ageing effect of rhamnose using in vitro reconstructed skin containing fibroblasts obtained either from young or old donors, and in vivo clinical investigation. Results: We detected positive effects of rhamnose in both epidermal and dermal compartments of in vitro reconstructed skin. Moreover, we were able to show that such in vitro findings were also obtained in vivo including an effect on collagen IV and procollagen I production. Conclusion: We provide evidence that rhamnose has a potentially beneficial effect on papillary dermis and dermal–epidermal junction, both of the areas which are affected by skin ageing. Abstract : Rhamnose has a potentially beneficial effect on papillary dermis and dermal–epidermal junction, both of the areas which are affected by skin ageing. RÉSUMÉ: Objectif: Le vieillissement de la peau humaine affecte particulièrement les fibroblastes du derme papillaire suggérant que le derme papillaire représente une zone importante altérée par le vieillissement. A partir de ces résultats, nous avons étudié le potentiel effet anti‐âge du rhamnose. Methodes: Le potentiel effet anti‐âge du rhamnose a été étudié in vitro en utilisant un modèle de peau reconstruite contenant des fibroblastes isolés à partir d'un donneur jeune et d'un donneur âgé et dans une étude clinique in vivo. Résultats: Nous avons observé un effet positif du rhamnose dans le compartiment épidermique et dermique de la peau reconstruite in vitro. En outre, nous avons pu montrer in vivo comme in vitro, un effet sur la production du collagène IV et du procollagène I. Conclusion: Le rhamnose a un effet bénéfique potentiel sur deux zones touchées par le vieillissement cutané, le derme papillaire et la jonction dermo‐épidermique.